Pengembangan Set Multipleks Penanda DNA Mikrosatelit untuk Analisis Variasi Genetik Padi dan Kedelai - Chaerani Chaerani; Nurul Hidayatun; Dwinita W. Utami (Jurnal AgroBiogen, 2009)
Detection of multiplex microsatellite markers in asingle capillary array on a laser detection system is traditionallyconducted with specific primers that are labelled withfluorescent dyes. An alternative method using fluorescentlabels that are appended to 5’ end of universal primer M13instead of to the specific primers offers flexibility indesignning multiplex panels and a less expensive method.Allele size range of microsatellite loci that can be grouped inmultiplex panels can be accurately estimated by pooling andanalyzing DNA samples from several genotypes simultaneously.This paper describes the procedure in developmentof microsatellite multiplex panels using M13 fluorescentlylabelledand estimation of allele size range based on pooledDNA strategies. Two multiplex panels of PCR amplificationproducts for rice consisting of 15 loci and three panels forsoybean consisting of 10 loci have been designed. Thepanels have been applied to 50 accessions of rice and soybeanwith fairly good results. Further characterization ofallele size range, however, is required prior to the applicationof these panels to diverse genotypes. The proceduredescribed here should be applicable in the development ofmultiplex panels of other species.